2009
DOI: 10.1111/j.1600-0404.1981.tb04421.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier integrity in patients with cerebral infarction investigated by computed tomography and serum-CSF-albumin

Abstract: Measurements of CSF-albumin, and S/CSF-albumin in two groups of patients with small and large infarcts failed to show BBB damage to albumin in about one half of the patients. N o significant difference was found between the two groups of patients in regard to the above-mentioned parameters. The localization of the infarcts (close to the CSF or deep in the brain) did not influence the S/CSF-albumin. No correlation was found between the S/CSF-albumin and the time interval between the onset of the stroke and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that CSF protein, CSF albumin and the AR can serve as an indicator of compromised BBB function in a variety of pathological conditions, among which stroke [25,26,27,28,29]. For this indication, the AR is superior to CSF protein or CSF albumin [25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that CSF protein, CSF albumin and the AR can serve as an indicator of compromised BBB function in a variety of pathological conditions, among which stroke [25,26,27,28,29]. For this indication, the AR is superior to CSF protein or CSF albumin [25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BBB abnormality occurred more frequently after thrombolytic therapy and was a predictor of subsequent hemorrhagic transformation and poor outcome [21,22,23,24]. Only 4 studies have evaluated the AR as a parameter for BBB dysfunction in ischemic stroke patients [25,26,27,28,29]. These studies date from the 1980s and 1990s, report on relatively small populations with sampling in the subacute phase of stroke and applied CT-based neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations